Transcriptional Regulation of the orf19 Gene and the tir-cesT-eae Operon of Enteropathogenic Escherichia coli - Sánchez-SanMartín, Claudia (American Society for Microbiology, 2001)
To establish an intimate interaction with the host epithelial cell surface, enteropathogenic Escherichia coli (EPEC) produces Tir, a bacterial protein that upon translocation and insertion into the epithelial cell membrane constitutes the receptor for intimin. The tir gene is encoded by the locus for enterocyte effacement (LEE), where it is flanked upstream by orf19 and downstream by the cesT and eae genes. With the use of a series of cat transcriptional fusions and primer extension analysis, we confirmed that tir, cesT, and eae form the LEE5 operon, which is under the control of a promoter located upstream from tir, and found that the orf19 gene is transcribed as a monocistronic unit. We also demonstrated that the LEE-encoded regulator Ler was required for efficient activation of both the tir and the orf19 promoters and that a sequence motif located between positions −204 and −157 was needed for the Ler-dependent activation of the tir operon. Sequence elements located between positions −204 and −97 were determined to be required for the differential negative modulatory effects exerted by unknown regulatory factors under specific growth conditions. Upon deletion of the upstream sequences, the tir promoter was fully active even in the absence of Ler, indicating that tir expression is subject to a repression mechanism that is counteracted by this regulatory protein. However, its full activation was still repressed by growth in rich medium or at 25°C, suggesting that negative regulation also occurs at or downstream of the promoter. Expression of orf19, but not of the tir operon, became Ler independent in an hns mutant strain, suggesting that Ler overcomes the repression exerted by H-NS (histone-like nucleoid structuring protein) on this gene.